Livestock Wastes - Cassou, Emilie (World Bank, Washington, DC, 2018)
The livestock sector is a major and growing source of pollution across the world as rising global demand for animal products including beef, pork, poultry, and dairy products is leading livestock operations to not only expand their output, but also to concentrate spatially, intensify, and separate from plant agriculture. Although livestock system outputs are growing faster than their spatial footprint—as managed grazing is giving way to confined, grain-based feeding—this pattern of development has major drawbacks and this note focuses on those related to animal wastes.1 In parts of both the developed and developing world, animal wastes have become a leading source of surface and ground water pollution as they are a major vector of unwanted nutrients, and alsocarry pathogens, antibiotics, hormones, heavy metals, other minerals, and pesticides. Through the release of particulate matter and other air pollutants, they are also a cause of foul odors, haze, acid rain, a loss of soil fertility, and air quality-related disease, while their potent greenhousegas emissions contribute to climate change.